The literary Churchill author, reader, actor - Rose, Jonathan 1952- (Yale University Press, 2014)
This literary biography introduces a Churchill we have not known before. Author Jonathan Rose explores in tandem Churchill's careers as statesman and author, revealing the profound influence of literature and theater on Churchill's personal, carefully composed grand story and on the decisions he made throughout his political life.Rose analyzes Churchill's writings and their reception (he won the Nobel Prize for Literature in 1953 and was a best- selling author), and chronicles his dealings with publishers, editors, literary agents, and censors. The book also identifies an array of authors who shaped Churchill's own writings and politics. Rose investigates the effect of Churchill's passion for heater on his approach to reportage, memoirs, and historical works.Perhaps most remarkably, Rose reveals the unmistakable influence of Churchill's reading on every important episode of his public life, including his championship of social reform, plans for the Gallipoli invasion, command during the Blitz, crusade for Zionism, and efforts to prevent a nuclear arms race. In conclusion, Rose traces the significance of Churchill's writings to later generations of politicians, among them President John F. Kennedy as he struggled to extricate the U.S. from the Cuban Missile Crisis.--From publisher description